2015
DOI: 10.1002/2014jd022479
|View full text |Cite
|
Sign up to set email alerts
|

Investigating diurnal and seasonal climatic response to land use and land cover change over monsoon Asia with the Community Earth System Model

Abstract: Land use and land cover change (LULCC) is primarily characterized as forest conversion to cropland for the development of agriculture. Previous climate modeling studies have demonstrated the LULCC impacts on mean climate and its long-term trends. This study investigates the diurnal and seasonal climatic response to LULCC in monsoon Asia through two numerical experiments with potential and current vegetation cover using the fully coupled Community Earth System Model. Results show that LULCC leads to a reduced d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 64 publications
3
47
0
1
Order By: Relevance
“…(Kumar et al, ; Lejeune et al, ; Pitman et al, ). Despite the existence of inconsistencies, most studies consistently concluded that LUCC (i.e., deforestation) could lead to more robust impacts on maximum ( T max ) and minimum temperature ( T min ) as well as other related extreme indices (e.g., diurnal temperature range) than mean temperature (Hua & Chen, ; Kalnay & Cai, ; P. J. Lawrence & Chase, ; X. Li et al, ; Voldoire & Royer, ; Xu et al, ; Zhang et al, ; Zhou et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…(Kumar et al, ; Lejeune et al, ; Pitman et al, ). Despite the existence of inconsistencies, most studies consistently concluded that LUCC (i.e., deforestation) could lead to more robust impacts on maximum ( T max ) and minimum temperature ( T min ) as well as other related extreme indices (e.g., diurnal temperature range) than mean temperature (Hua & Chen, ; Kalnay & Cai, ; P. J. Lawrence & Chase, ; X. Li et al, ; Voldoire & Royer, ; Xu et al, ; Zhang et al, ; Zhou et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In this area, explore the climatic effects of land use cover change (LUCC) [14,37,[40][41][42][43]. The results from the simulations using actual albedo, LAI, and VF indicated that LUCC led to local cooling of 1 • C in the summer and local warming exceeding 0.8 • C in the winter.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the nonlinear responses in the CAM5.1‐SOM experiment, involving the oceanic feedbacks, are somewhat different from those in 1 × EXPT. It was reported that rainfall responses to anthropogenic forcing presented in ocean‐atmosphere coupled models show distinct features from those in the stand‐alone AGCMs [ Chung et al ., ; Wang et al ., ; Ma et al ., ; Xu et al ., ]. As a result, further investigation is needed to explore how the ocean‐atmosphere coupling effect modulates fast responses to the nonlinear interaction seen in 1 × EXPT.…”
Section: Discussionmentioning
confidence: 99%